FARMASI PLASMA - Gita Cahya Eka Darma (Universitas Islam Bandung, 2022)
In the last decade, the world has recognized the existence of a new branch of science in the field of medicine that uses plasma technology in the process, namely plasma medicine. A science that examines plasma as a drug in the form of a medical device or method in medical technology. The use of the term plasma medicine into Indonesian is one of the objectives of this study, because if it is translated into